The Effect of Learning Motivation and Roboguru Integration on Metacognition in Independent Learning - Rezky Hardianingsih; Haryanto, Haryanto (Yayasan Payungi Smart Madani, 2025)
This study examines the influence of learning motivation and the frequency of Roboguru usage on students' metacognitive skills in independent learning. Using a quantitative approach, data were collected from 100 grade XI students at SMA Negeri 21 Makassar through questionnaires and analyzed using multiple linear regression. The results indicate that both learning motivation (β = 0.661, p < 0.05) and Roboguru usage intensity (β = 0.116, p < 0.05) significantly and positively affect metacognitive skills. Together, these factors explain 49.9% of the variance in metacognitive abilities (R² = 0.499), with learning motivation having a stronger impact. These findings align with Self-Determination Theory and social-cognitive motivation theory, highlighting the importance of intrinsic motivation and adaptive technology in fostering self-regulated learning. The study suggests that enhancing students' learning motivation while strategically integrating digital tools like Roboguru can improve metacognitive skills, thereby supporting more effective independent learning. Practical implications include the need for teacher guidance, parental support, and structured digital learning strategies to optimize metacognitive development. This study's novelty lies in examining the combined influence of learning motivation and the digital platform Roboguru on metacognitive skills, which remains underexplored in independent learning contexts. Its key contribution is providing empirical evidence that integrating intrinsic motivation with adaptive technology significantly enhances students' metacognitive abilities, while offering practical recommendations for educators and parents on structured digital tool utilization.